Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja: Studi pada Pegawai Dinas Perindustrian, Transmigrasi dan Tenaga Kerja Kabupaten Purworejo - Rohman, Khoirul; Hardin, Hardin; Utomo, Agus Saur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Human resource management is believed to play a crucial role in an organization's competitive success. This role is greatly influenced by the participation of its employees, which must be optimally managed. Furthermore, human resource management is believed to enhance employee contributions to the organization, thereby achieving desired performance. Performance can be influenced by various factors, such as work discipline and the work environment. The purpose of this study was to examine the effect of work discipline on the performance of employees at the Department of Industry, Transmigration, and Manpower of Purworejo Regency, and the influence of the work environment on the performance of employees at the Department of Industry, Transmigration, and Manpower of Purworejo Regency. The population in this study was employees at the Department of Industry, Transmigration, and Manpower of Purworejo Regency. The sampling technique used purposive sampling, with 65 participants. Data collection used a questionnaire, which was tested for validity and reliability. Hypotheses were tested using multiple linear regression analysis. Based on the results of the research and discussion, it can be concluded that: work discipline has a positive and significant effect on the performance of employees of the Department of Industry, Transmigration and Manpower of Purworejo Regency, and the work environment has a positive and significant effect on the performance of employees of the Department of Industry, Transmigration and Manpower of Purworejo Regency.